use special exercises training Recurring manner according to the concentration of lactic acid in the blood and its impact in carrying your speed and accomplish ran 400 meters - Faaq, Haider (Journal of Physical Education, 2015)
The importance of research in a study of the coaches athletics help in rationing training loads using a device that measures the concentration of lactic acid in the blood after, and through the use of exercises in a manner training Recurring to the evolution of carrying speed your effectiveness ran 400 The aim of the research into the numbers of special training in a manner Training Recurring and codified according to the concentration of lactic acid in the blood to carry speed the development of your least and most of the race and ran a distance of 400 meters. The researcher used the experimental method with the design of the two experimental groups with pre and posttests, the research sample - has been selected in the manner intentional (12) Runner of the best runners effectiveness ran 400 meters in Iraq and the category of Commons, and then deliberately researcher to divide them into two groups of equal experimental and control group. The researcher concluded that there are significant differences were statistically significant in the test ran carrying speed race distance of at least 300 meters and ran a test of achievement as well as the concentrations of lactic acid in the blood, while not Tdahr these differences in moral tolerance test speed of the longest distance race ran 600 meters